Implementation status of ecological solid waste management act of 2000 (RA 9003) in Boracay Island the case of a small tourist island - Ibabao, Rhodella A.; Casimero, Juvy M. (Danyag :the UPV journal of humanities and social sciences, 2008)
"The study sought to evaluate the implementation of Republic Act 9003 to provide recommendations for improved solid waste management practices in the small tourist island-Boracay. Specifically, it aimed to describe the current state of solid waste mangement (SWM) in Boracay and the participation of the Local Government Unit (LGU) as well as the barangays in the implementation of RA 9003. It also discussed the challenges they faced in the implementation and raised applicable solutions to address these challenges. Data were gathered through focus group discussions (FGCs), key informants interview (KII), and on-site observation. A survey conducted on people's perceptions on waste management in the island showed that Information and Education Campaign (IEC) in the island has been successful in integrating the SWM program into the school curriculum by allowing greater participation from school children and youth in its implementation. However, the IEC initiatives have fallen short in reinforcing awareness on how to manage and reduce solid waste among the people. The results further showed that IEC advocates themselves lacked proper training and exposure. Law enforcements relative to waste management were not strict in looking for violators; infrastructure hinders collection of waste from source; while budgetary constraints pose threats on the sustainability of the program."